2017
DOI: 10.1097/iae.0000000000001408
|View full text |Cite
|
Sign up to set email alerts
|

Change of Choroidal Volume in Untreated Central Serous Chorioretinopathy

Abstract: In this study, an increase in SRF was associated with an increase in both choroidal thickness and volume in eyes with treatment-naïve CSC. Eyes with thicker baseline choroidal volume showed a greater reduction in SRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Moreover, eyes with higher baseline choroidal volume also responded better with more reduction in SRF. 43 …”
Section: Imaging Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, eyes with higher baseline choroidal volume also responded better with more reduction in SRF. 43 …”
Section: Imaging Parametersmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Choroidal volume. Pertl and colleagues 43 showed that in eyes with treatment-naïve CSCR, changes in CT and volume correlated with changes in subretinal fluid (SRF). Moreover, eyes with higher baseline choroidal volume also responded better with more reduction in SRF.…”
Section: Octmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SDOCT and OCT Angiography (OCTA) are allowing for new insights in the investigation of vascular and circulatory conditions in different chorioretinal disorders, including CSC [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SDOCT and OCT Angiography (OCTA) are allowing for new insights in the investigation of vascular and circulatory conditions in different chorioretinal disorders, including CSC [ 9 , 17 , 18 , 19 ]. In particular, OCTA is a dye-free technique that is able to analyze separately the different retinal vascular layers, the CC, and possible associated neovascular lesions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%